2017 13th International Wireless Communications and Mobile Computing Conference (IWCMC) 2017
DOI: 10.1109/iwcmc.2017.7986431
|View full text |Cite
|
Sign up to set email alerts
|

Towards the deployment of a fully centralized Cloud-RAN architecture

Abstract: Abstract-In the framework of Network Function Virtualization (NFV), we address in this work the design and sizing of Cloud-RAN architectures. We concretely investigate the execution time of software-based Base Band Units (BBUs) on multicore systems. Since Cloud-RAN requires a real-time behavior, we use parallel programming techniques in order to minimize the runtime of BBU functions. For an efficient utilization of computing resources, we investigate the relevance of resource pooling where a global scheduling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…A more generalized processing-time model was introduced in [8], it does not only consider the MCS index as in [7], but also the number of Resource Blocks and the CPU frequency. In the context of Cloud-RAN, the effect of paralleling decoding functions has been considered in [9]; the authors demonstrated the ability of parallelism to reduce the run-time.…”
Section: Related Workmentioning
confidence: 99%
“…A more generalized processing-time model was introduced in [8], it does not only consider the MCS index as in [7], but also the number of Resource Blocks and the CPU frequency. In the context of Cloud-RAN, the effect of paralleling decoding functions has been considered in [9]; the authors demonstrated the ability of parallelism to reduce the run-time.…”
Section: Related Workmentioning
confidence: 99%
“…Figure 1(a) shows the legacy solution for logic split of BBU functionalities [6], [7]. The ground layer consists of radio frequency processing (RF), for Analog-Digital and Digital-Analog conversion of received signals.…”
Section: System Preliminariesmentioning
confidence: 99%
“…Whole baseband processing of legacy 4G network requires a general threshold of 3 ms to be completed (may be extended to 4 ms but at an eventual higher price in terms of errors) [6], [7]. Moreover, HARQ employs acknowledgements with FEC using concatenated convolutional codes of variable rate (normally between 1/3 and 1/2) with turbo decoding: especially, Layer 3 should target a BER less than 10 -5 .…”
Section: System Preliminariesmentioning
confidence: 99%
“…In this new paradigm, denoted as Cloud-RAN (Radio Access Network), instead of being executed on dedicated hardware close to the antennas, all the digital data processing would be performed on centralized large scale programmable processors arrays. This would allow a dynamic balancing of the computational effort within the network [6,20,22,26,27].…”
Section: Introductionmentioning
confidence: 99%